Adults data - Czorlich, Yann; Aykanat, Tutku; Erkinaro, Jaakko; Orell, Panu; Primmer, Craig R. (Dryad Digital Repository, 2018)
Data associated with the article: Czorlich Y., Aykanat T., Erkinaro J., Orell P. & Primmer C.R. (2018) Rapid sex-specific evolution of age at maturity is shaped by genetic architecture in Atlantic salmon. Nature Ecology & Evolution. Table including the genotypes of adults (row) at 190 loci and additional informations (e.g. spawning year, sex)